Sugarcane Selection for Sucrose and Tonnage Using Economic Criteria - José Alvarez; Chris W. Deren; Barry Glaz (EDIS)
The objectives of this document (mainly based on Alvarez, et al., 2003) are to illustrate the use of an economic index in selecting clones that are somewhat ambiguous in merit (mid-to-low rankings in TCA or SC) and to show how the relationship between TCA and SC can differ when viewed from an economic, rather than a biological, perspective. This is EDIS document FE476, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published May 2004.